Upaya Santri Dalam Pemeliharaan Hafal Al- Qur’an Di MANU Kota Gede Yogyakarta - Ahlan Abdullah Solo; Taufik Nugroho; Difla Nadjih (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2018)
The research aimed to find out the implementation of the Muraja'ah method in memorizing Al-Qur'an in Kotagede Yogyakarta's Aliyah Nurul Ummah Madrasah (MANU) in order to identify the supporting and inhibiting factors experienced by the santri including how they overcome the inhibiting factors. MANU santri students always do the Koran memorization with a target every day is one page without counting how many verses are memorized. The method is useful for maintaining memorization of the Qur'an and does not interfere with teaching and learning activities in boarding schools